2013
DOI: 10.3233/jad-130218
|View full text |Cite
|
Sign up to set email alerts
|

Prion Protein Regulates Iron Transport by Functioning as a Ferrireductase

Abstract: Prion protein (PrPC) is implicated in the pathogenesis of prion disorders, but its normal function is unclear. We demonstrate that PrPC is a ferrireductase (FR), and its absence causes systemic iron deficiency in PrP knock-out mice (PrP−/−). When exposed to non-transferrin-bound (NTB) radioactive-iron (59FeCl3) by gastric-gavage, PrP−/− mice absorb significantly more 59Fe from the intestinal lumen relative to controls, indicating appropriate systemic response to the iron deficiency. Chronic exposure to excess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 49 publications
1
74
0
Order By: Relevance
“…Interestingly mice lacking the gene showed signs of systemic iron deficiency (Singh et al 2009b) and a progressive decrease of the metal is described in brains from affected patients or animals, despite an increase in total iron load (Singh et al 2009a) together with loss of function of PrPC. There is evidence that PrPc could have ferroxidase activity and its absence could reduce iron uptake in diseased brain (Singh et al 2013), but an important role could be attributed to the formation of aggregates between the PrPsc and iron-rich ferritin (Singh et al 2012). The ferritin isolated form affected brains is insoluble and retains iron even when exposed to harsh denaturing conditions.…”
Section: Ferritin In Brain Disorders With Altered Iron Homeostasismentioning
confidence: 99%
“…Interestingly mice lacking the gene showed signs of systemic iron deficiency (Singh et al 2009b) and a progressive decrease of the metal is described in brains from affected patients or animals, despite an increase in total iron load (Singh et al 2009a) together with loss of function of PrPC. There is evidence that PrPc could have ferroxidase activity and its absence could reduce iron uptake in diseased brain (Singh et al 2013), but an important role could be attributed to the formation of aggregates between the PrPsc and iron-rich ferritin (Singh et al 2012). The ferritin isolated form affected brains is insoluble and retains iron even when exposed to harsh denaturing conditions.…”
Section: Ferritin In Brain Disorders With Altered Iron Homeostasismentioning
confidence: 99%
“…It is remarkable that the majority of PrP C in the urine is similar to the anchorless, N-terminally processed form observed in human and animal brains and neuronal cell models, suggesting similar processing of PrP C by kidney epithelial and cortical neuronal cells (20 -22). More importantly, the presence of PrP C in the urine of healthy individuals suggests that it is expressed on PT cells where it may provide FR activity necessary for the uptake of Tf-iron and NTBI (4,5,17).…”
Section: Prion Protein (Prpmentioning
confidence: 99%
“…However, excess NTBI and hemin aggregate PrP C to a detergent-insoluble form, preventing further iron uptake. 59 Fe-citrate diluted in normal saline as described in previous reports (5,25). For the specific radiolabeling of NTBI, serum Tf was saturated with excess unlabeled iron by injecting ferric-ammonium citrate (FAC) (70 g/22 g of mouse) intraperitoneally followed by 59 Fe-citrate after an interval of 30 min (26).…”
Section: Prion Protein (Prpmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the changes in uptake and storage of iron suggested by these studies, it has also been suggested that PrP c itself is a ferrireductase (Figure 1) , which is then more likely to be transported into the cell, thus resulting in increased cellular iron. However, unlike alpha-synuclein, for which kinetic studies on purified protein suggested iron reduction is a result of true enzymatic catalysis109], studies on the ferrireductase activity of PrP c have only been performed on cell extracts [140]. As PrP c has already been suggested to be associated with redox balance in cells [123], this observation may only be reporting a secondary effect rather than a direct function of PrP c in iron reduction.…”
Section: Prion Diseasesmentioning
confidence: 99%